Incidence rate of tuberculosis among HIV infected children in Ethiopia: systematic review and meta-analysis - Desalegn Girma; Zinie Abita; Nigusie Shifera; Mulugeta Wodaje Arage; Biruk Beletew Abate; Melsew Setegn Alie; Gossa Fetene Abebe (BMC, 2024)
Abstract Background Tuberculosis is one the leading causes of death from a single infectious disease, caused by the bacillus mycobacterium tuberculosis. In Ethiopia, even though several primary studies have been conducted on the incidence of tuberculosis among HIV-infected children, the pooled incidence rate of tuberculosis among HIV-infected children (aged 0-14 years) is unknown. Therefore, the main objectives of this systematic review and meta-analysis are to estimate the pooled incidence rate of tuberculosis among HIV-infected children and its predictors in Ethiopia. Method International electronic databases such as PubMed, HINARI, Science Direct, Google Scholar, and African Journals Online were searched using different search engines.  Quality of primary studies was checked using the Joanna Briggs Institute checklist. The heterogeneity of studies was tested using I-square statistics. Publication bias was tested using a funnel plot and Egger's test. Forest plots and tables were used to present the results. The random effect model was used to estimate the pooled incidence of tuberculosis among children living with HIV. Result A total of 13 studies were included in this systematic review and meta-analysis. The pooled incidence of tuberculosis among HIV-infected children was 3.77 (95% CI: 2.83, 5.02) per 100-person-year observations. Advanced HIV disease (HR: 2.72, 95% CI: 1.9; 3.88), didn't receive complete vaccination (HR: 4.40, 95% CI: 2.16; 8.82), stunting (HR: 2.34, 95% CI: 1.64, 3.33), underweight (HR: 2.30, 95% CI: 1.61; 3.22), didn't receive Isoniazid preventive therapy (HR: 3.64, 95% CI: 2.22, 5.96), anemia (HR: 3.04, 95% CI: 2.34; 3.98), fair or poor antiretroviral therapy adherence (HR: 2.50, 95% CI: 1.84; 3.40) and didn't receive cotrimoxazole preventive therapy (HR: 3.20, 95% CI: 2.26; 4.40) were predictors of tuberculosis coinfection among HIV infected children. Conclusion This systematic review and meta-analysis concluded that the overall pooled incidence rate of tuberculosis among HIV-infected children was high in Ethiopia as compared to the END TB strategy targets. Therefore, emphasis has to be given to drug adherence (ART and Isoniazid) and nutritional counseling. Moreover, early diagnosis and treatment of malnutrition and anemia are critical to reduce the risk of TB coinfection. Registration Registered in PROSPERO with ID: CRD42023474956.